Understanding Educators’ Hesitation to Adopt Tailored Digital Gamification - H.L. Duong; T.K. Vo (Психологическая наука и образование)
Tailored digital gamification holds significant promise for enhancing student engagement and learning outcomes. However, its adoption by Vietnamese lecturers remains limited. This qualitative study investigates the reasons behind their reluctance to embrace tailored digital gamification and explores the role of cultural factors. Interviews were conducted with lecturers from six universities in Vietnam. Findings reveal a preference for traditional teaching methods due to their familiarity and perceived effectiveness. Barriers to adoption include perceived complexity, lack of training, and concerns about content development. Additionally, cultural factors such as hierarchy-authority, gaming perception, and collectivism were found to significantly influence lecturers' attitudes towards gamification. This research provides crucial insights into the complex challenges and factors hindering digital gamification adoption in Vietnamese universities, informing the targeted interventions to facilitate the successful integration of digital gamification into the Vietnamese landscape.